Reinforced Concrete Box Beam Strengthened By Carbon-Fiber-Reinforced Polymer Subjected To Combined Shear And Torsion - Shengqiang, Ma (2017)
Box beams, with high torsional stiffness, light weight, and great structural resistance, are popularly used in the bridge structures. However, these box beams may fail suddenly due to increased traffic volumes and loads and diminished capacity from deterioration. Fiber-reinforced polymer (FRP) strengthening technique has been studied and used in structures to improve the flexural and shear capacity of beams. However, very few strengthening studies have paid much attention to reinforced concrete (RC) box beams subjected to shear, torsion, and combined shear and torsion. Therefore, in this research, three sets of experiments on RC box beams strengthened with the carbon-fiber-reinforced polymer (CFRP) in shear, pure torsion, and combined shear and torsion were conducted. Based on experiments, the main aims are to: (a) predict the shear contribution of CFRP; (b) evaluate the strengthening effectiveness and predict the CFRP contribution to torsion; (c) investigate the behavior of strengthened box beams subjected combined shear and torsion and develop mathematical equations to predict strength. The fib Bulletin 14 model with the reduction coefficient proposed in effective strain of fiber could reliably predict the shear CFRP contribution to shear in strengthened RC box beam. In addition, it was found that the configuration of U-jacketing with longitudinal strips had a better performance in the torsional strengthening of RC box beam. One combined model had been revealed to be reliable and conservative in calculating the torsional strength of retrofitted RC beams. Further on, strengthening effectiveness of CFRP in combined shear and torsion to RC box beams was inversely proportional to torque-to-shear ratio. The derived equations with modified model of effective strain in fiber could give the desirable results of torsional strength to the strengthened or unstrengthened RC box beams subjected combined action.